Current challenges of severe acute respiratory syndrome coronavirus 2 seroprevalence studies among blood donors: A scoping review. Issue 4 (3rd December 2021) - Saeed, Sahar; Uzicanin, Samra; Lewin, Antoine; Lieshout‐Krikke, Ryanne; Faddy, Helen; Erikstrup, Christian; Osiowy, Carla; Seed, Clive R.; Steele, Whitney R.; Davison, Katy; Custer, Brian; O'Brien, Sheila F.; et al.
Abstract: Background and Objectives: Blood donors are increasingly being recognized as an informative resource for surveillance. We aimed to review severe acute respiratory syndrome coronavirus 2 seroprevalence studies conducted among blood donors to investigate methodological biases and provide guidance for future research. Materials and Methods: We conducted a scoping review of peer‐reviewed and preprint publications between January 2020 and January 2021. Two reviewers used standardized forms to extract seroprevalence estimates and data on methodology pertaining to population sampling, periodicity, assay characteristics, and antibody kinetics. National data on cumulative incidence and social distancing policies were extracted from publicly available sources and summarized. Results: Thirty‐three studies representing 1, 323, 307 blood donations from 20 countries worldwide were included (sample sizes ranged from 22 to 953, 926 donations). The majority of the studies (79%) reported seroprevalence rates <10% (ranging from 0% to 76% [after adjusting for waning antibodies]). Overall, less than 1 in 5 studies reported standardized seroprevalence rates to reflect the demographics of the general population. Stratification by age and sex were most common (64% of studies), followed by region (48%). A total of 52% of studies reported seroprevalence at a single time point. Overall, 27 unique assay combinations were identified, 55% of studies used a single assay and only 39% adjusted seroprevalence rates for imperfect test characteristics. Among the nationally representative studies, case detection was most underrepresented in Kenya (1:1264). Conclusion: By the end of 2020, seroprevalence rates were far from reaching herd immunity. In addition to differences in community transmission and diverse public health policies, study designs and methodology were likely contributing factors to seroprevalence heterogeneity.